The comparative research of transaminase activity in the chickens blood, infected with Eimeria tenella and treated with baycox - Ахмедов, Е. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The experiments have been carried out on 20 day old local black rock chickens in the laboratory of biochemical basis of host-parasite relationships of the Institute of Zoology of ANAS. The study of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in blood serum of chickens infected with a parasite E. tenella in a dose of 20,000 sporulated oocysts and treated with baycox 2.5% in doses of 1 ml/l, 2 ml/l and 3 ml/l has showed that decrease of activity of both enzymes in chickens infected and untreated and treated with three doses of the drug has short term nature. On the 5th and 7th days of invasion AST and ALT activities in blood serum of chickens, infected and treated with baycox in a dose of 1 ml/l and 3 ml/l, increased. On the 10th day activity of enzymes returned to normal. It has been found that in the group of chickens, treated with baycox in a dose of 3 ml/l on 3, 5, and 7th days of invasion, AST activity is higher for 0.22, 0.31 and 0.28 mcmol, and ALT activity is higher for 0.06, 0.05 and 0.07 mcmol in comparison with infected and untreated chickens. These data confirm hepatotoxic influence of 3 ml/l baycox dose. Thus, AST and ALT activities in blood serum of chickens treated with baycox in a dose of 2 ml/l decrease in comparison with infected and untreated ones. It has been also revealed that baycox in a dose of 2 ml/l keeps activity of these enzymes in normal.